Attain Cultural Integration through teachers' Conflict Resolution skills Development: The ACCORD Project - Marocco, Davide; Dell'Aquila, Elena; Zurlo, Maria Clelia; Vallone, Federica; Barajas, Mario; Frossard, Frederique; Di Ferdinando, Andrea; Di Fuccio, Raffaele; Lippens, Michiel; Van Praag, Lore; Protopsaltis, Aristidis; Swertz, Christian; et al. (QWERTY, 2019)
Scenario-based learning (SBL) has recently received more and more attention in the training and education fields as a mechanism for providing active and generative learning. E-learning systems can provide a solid platform upon which SBL can be created and used to promote relational competences development, and to offer open source e-learning tools so to overcome common lack of access to affordable training resources. Within this paper a project called ACCORD to develop a new e-learning system to promote intercultural skills in terms of intercultural literacy, inclusive education and conflict management will be described. This project aims to prepare secondary school teachers from five European countries (Austria, Belgium, Germany, Italy, Spain) to take an active stand against intercultural conflicts within the school context, by providing SBL and game-based learning approach. The present article will provide an overview of the ACCORD project, highlighting the theoretical framework underpinning its development, the methodologies that have been used, and the main preliminary outcomes.
CRIS-Team WoS Importer:2020-02-18